PORTRAIT (Patient-Centered Outcomes Related to Treatment Practices in Peripheral Arterial Disease: Investigating Trajectories). Issue 2 (February 2018) - Smolderen, Kim G.; Gosch, Kensey; Patel, Manesh; Jones, W. Schuyler; Hirsch, Alan T.; Beltrame, John; Fitridge, Rob; Shishehbor, Mehdi H.; Denollet, Johan; Vriens, Patrick; Heyligers, Jan; Stone, MEd, Nancy; et al.
Abstract : Background: Health status outcomes, including symptoms, functional status, and quality of life, are critically important outcomes from patients' perspectives. The PORTRAIT study (Patient-Centered Outcomes Related to Treatment Practices in Peripheral Arterial Disease: Investigating Trajectories) was designed to prospectively define health status outcomes and examine associations between patients' characteristics and care to these outcomes among those presenting with new-onset or worsened claudication. Methods and Results: PORTRAIT screened 3637 patients with an abnormal ankle-brachial index and new, or worsened, claudication symptoms from 16 peripheral arterial disease (PAD) specialty clinics in the United States, the Netherlands, and Australia between June 2, 2011, and December 3, 2015. Of the 1608 eligible patients, 1275 (79%) were enrolled. Before treatment, patients were interviewed to obtain their demographics, PAD symptoms and health status, psychosocial characteristics, preferences for shared decision-making, socioeconomic, and cardiovascular risk factors. Patients' medical history, comorbidities, and PAD diagnostic information were abstracted from patients' medical records. Serial information about patients' health status, psychosocial, and lifestyle factors was collected at 3, 6, and 12 months by a core laboratory. Follow-up rates ranged from 84.2% to 91%. Clinical follow-up for PAD-related hospitalizations and major cardiovascular events is ongoing. Conclusions: PORTRAIT systematically collected serial PAD-specific health status data as a foundation for risk stratification, comparative effectiveness studies, and clinicians' adherence to quality-based performance measures. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01419080. Abstract : Supplemental Digital Content is available in the text.